2022
DOI: 10.3390/app12083853
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Selected Technological Parameters’ Influences on the Tribological Properties of Products Manufactured Using the FFF Technique

Abstract: This study investigates how layer deposition in printing 3D models made of polyetherimide (PEI) using the fused filament fabrication (FFF) technique affects resistance of these models to abrasive wear. Samples made by additive manufacturing with different setting of build orientation and path generation strategy of extruded fibers were used in the experiment. The experiments were conducted on a tribometer according to the ASTM G65-16 standard. The friction force, normal force, and temperature in the contact ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Garnet abrasive was used in this experiment. Garnet sand is a natural material [ 24 ]. The composition of the abrasive used is shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garnet abrasive was used in this experiment. Garnet sand is a natural material [ 24 ]. The composition of the abrasive used is shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A study by Mitaľ et al [ 24 ] investigated the influence of processing parameters on wear performance of 3D printed parts. Abrasion resistance of PEI material showed the suitability of the chosen build orientation and deposition strategy for the production of parts by additive manufacturing, depending on the required tribological properties such as friction coefficient and wear behavior at 3D printing technological parameters such as layer height of 0.254 mm and filament width of 0.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigations have been carried out on polylactic acid (PLA) [79,80,[84][85][86], which is very widely used in the AM industry, as a composite with bronze particles [87], silicon [84], and HT-PLA [86], which is suitable for higher temperatures. Finally, the following materials represented the research object of the considered publications and were investigated in detail with regard to their tribological behavior: polyethylene terephthalate glycol (PETG) [80,86,88], polybutylene terephthalate (PBT) [89], polyether sulfone (PES) [90], PES/BF (basalt fiber reinforced) [90], polyetherimide (PEI) [91], and acrylonitrile styrene acrylate (ASA) [92].…”
Section: Extrusion-based Additive Manufacturing (Eam)mentioning
confidence: 99%
“…In conclusion, COF and wear rate increased with an increase in the printing temperature or layer thickness for ASA-printed specimens. A further polymer being investigated was PEI, which was FFF-printed with different build directions and layer deposition strategies and tested under dry conditions with an Fe 3 Al 2 (SiO 4 ) 3 garnet abrasive [91]. The study indicated that printing in the horizontal orientation (X) and a layer deposition strategy of 0 • and 90 • reduced material wear and concomitantly exhibited a low COF.…”
Section: Extrusion-based Additive Manufacturing (Eam)mentioning
confidence: 99%
“…A study by Mital' et al [24] investigated the influence of processing parameters on wear performance of 3D printed parts. Abrasion resistance of PEI material showed the suitability of the chosen build orientation and deposition strategy for the production of parts by additive manufacturing, depending on the required tribological properties such as friction coefficient and wear behavior at 3D printing technological parameters such as layer height of 0.254 mm and filament width of 0.5 mm.…”
Section: Of 20mentioning
confidence: 99%